Legal Opportunities Solutions to Tackle the Deficit in Indonesia’s National Health Insurance Program - Arimbi, Diah (Faculty of Law, Universitas Padjadjaran, 2024)
Indonesia's National Health Insurance program faces significant challenges, including financial deficits and declining membership, managed by the Social Security Administrative Body for Health (BPJS Kesehatan). This study explores legal opportunities for alternative funding to address these issues. It employed a normative juridical approach with secondary, primary, and tertiary legal sources to examine the implementation of the Law Number 24 of 2011 and the Government Regulation Number 53 of 2018. Although cigarette tax collection regulations aim to realize health funding, there are no optimal results. However, Indonesian law offers extensive opportunities, such as increasing cigarette excise rates, leveraging corporate social responsibility, and engaging in creative funding collaborations with the government, private sector, non-governmental organizations (NGOs), and communities. These strategies are proposed to mitigate the deficit, expand participant coverage, enhance the National Health Insurance program's quality, and improve overall health standards.